From Flying Geese to Leading Dragons New Opportunities and Strategies for Structural Transformation in Developing Countries - Lin, Justin Yifu (The World Bank, 2011)
Economic development is a process of continuous industrial and technological upgrading in which any country, regardless of its level of development, can succeed if it develops industries that are consistent with its comparative advantage, determined by its endowment structure. The secret winning formula for developing countries is to exploit the latecomer advantage by building up industries that are growing dynamically in more advanced fast growing countries that have endowment structures similar to theirs. By following carefully selected lead countries, latecomers can emulate the leader-follower, flying-geese pattern that has served well successfully catching-up economies since the 18th century. The emergence of large middle-income countries such as China, India, and Brazil as new growth poles in the world, and their dynamic growth and climbing of the industrial ladder, offer an unprecedented opportunity to all developing economies with income levels currently below theirs-including those in Sub-Saharan Africa. Having itself been a "follower goose," China is on the verge of graduating from low-skilled manufacturing jobs and becoming a "leading dragon." That will free up nearly 100 million labor-intensive manufacturing jobs, enough to more than quadruple manufacturing employment in low-income countries. A similar trend is emerging in other middle-income growth poles. The lower-income countries that can formulate and implement a viable strategy to capture this new industrialization opportunity will set forth on a dynamic path of structural change that can lead to poverty reduction and prosperity